Bangladesh Rural Advancement Committee accounts for the year/period ended 31 December 1987 - BRAC (© BRAC, 2016)
This Financial Statement prepared by Baree Pear & Co. Chartered Accountants, 34 Mirpur road (2nd floor), Dhanmondi, Dhaka-5.